Effects of supplemental hybrid bacterial 6-phytase in low-energy, inorganic phosphorus-free hen diets on laying performance, egg quality, and bone strength - Pinar Sacakli; Muhammad Shazaib Ramay; Ahmet Ceylan; Özge Özgenç Çınar; Fatma Kübra Erbay Elibol; Josoa André Harijaona; Yauheni Shastak; Peter Ader; Dieter Feuerstein; Ali Calik (PLoS ONE, 2025)
A 22-week trial was conducted to assess the effects of replacing inorganic phosphorus (P) with two levels of a hybrid bacterial 6-phytase in low-energy diets for laying hens, from 23 to 44 weeks of age. The study focused on hen performance, egg quality and bone health of laying hens. For this purpose, Lohmann Brown Classic hens (n = 432) were randomly allocated to four dietary groups, each comprising nine replicates of 12 birds. The groups included: (1) positive control (PC), a standard diet containing 3.7% calcium, 0.38% non-phytate phosphorus (nPP) and 2730 kcal/kg metabolizable energy (ME), (2) negative control (NC), a diet similar in nutritional specifications to the PC but with reduced nPP (0.12%) and ME (2630 kcal/kg), (3) NC300 and (4) NC600, where NC diets were supplemented with 300 and 600 phytase unit (FTU) per kg feed, respectively. All diets were provided as mash and formulated using corn, soybean meal and sunflower meal as the main ingredients. The NC diet significantly impaired hen performance compared to the PC diet (p < 0.05). Specifically, the NC diet led to deterioration in egg production (p < 0.001), egg weight (p = 0.001), egg mass (p < 0.001), feed intake (p < 0.001), feed conversion ratio (p = 0.002), body weight (p < 0.001), and livability (p = 0.036). Additionally, the NC diet increased the incidence of cracked (p < 0.001) and shell-less eggs (p < 0.001) and lowered eggshell breaking strength (p = 0.005). Bone health was also adversely affected by the NC diet, as indicated by reduced tibia ash content (p < 0.001), stiffness (p = 0.005), and maximum load-bearing capacity (p = 0.040). Moreover, with NC diet, there was a decrease in osteoprotegerin (OPG) expression (p < 0.001) and an increase in receptor activator of nuclear factor kappa-B ligand (RANKL) expression (p < 0.001) in tibia, resulting in a greater RANKL/OPG ratio (p < 0.001). Supplementing the NC diet with bacterial 6-phytase at both levels (300 and 600 FTU/kg) effectively mitigated all adverse effects of P and ME deficiency on the aforementioned parameters, bringing them to levels comparable to those of the PC. Notably, the 600 FTU/kg supplementation provided slightly better results in terms of egg weight and eggshell breaking strength than the 300 FTU/kg level. Overall, this study suggests that supplementing the hybrid bacterial 6-phytase (300–600 FTU/kg) to P-deficient (0.12% nPP) and low energy (−100 kcal/kg) diets can fully replace inorganic P without compromising laying performance, egg quality, or bone health. Further research is recommended to determine the optimal levels of hybrid bacterial 6-phytase in P-deficient diets for laying hens throughout laying cycle of the birds with other nutrient matrices (energy, amino acids, calcium) to optimize layer feed formulations.